Human Induced Pluripotent Stem Cell‐Derived Microvesicles Transmit RNAs and Proteins to Recipient Mature Heart Cells Modulating Cell Fate and Behavior. (24th June 2015) - Bobis‐Wozowicz, Sylwia; Kmiotek, Katarzyna; Sekula, Malgorzata; Kedracka‐Krok, Sylwia; Kamycka, Elzbieta; Adamiak, Marta; Jankowska, Urszula; Madetko‐Talowska, Anna; Sarna, Michal; Bik‐Multanowski, Miroslaw; Kolcz, Jacek; Boruczkowski, Dariusz; et al.
Abstract: Microvesicles (MVs) are membrane‐enclosed cytoplasmic fragments released by normal and activated cells that have been described as important mediators of cell‐to‐cell communication. Although the ability of human induced pluripotent stem cells (hiPSCs) to participate in tissue repair is being increasingly recognized, the use of hiPSC‐derived MVs (hiPSC‐MVs) in this regard remains unknown. Accordingly, we investigated the ability of hiPSC‐MVs to transfer bioactive molecules including mRNA, microRNA (miRNA), and proteins to mature target cells such as cardiac mesenchymal stromal cells (cMSCs), and we next analyzed effects of hiPSC‐MVs on fate and behavior of such target cells. The results show that hiPSC‐MVs derived from integration‐free hiPSCs cultured under serum‐free and feeder‐free conditions are rich in mRNA, miRNA, and proteins originated from parent cells; however, the levels of expression vary between donor cells and MVs. Importantly, we found that transfer of hiPSC components by hiPSC‐MVs impacted on transcriptome and proteomic profiles of target cells as well as exerted proliferative and protective effects on cMSCs, and enhanced their cardiac and endothelial differentiation potential. hiPSC‐MVs also transferred exogenous transcripts from genetically modified hiPSCs that opens new perspectives for future strategies to enhance MV content. We conclude that hiPSC‐MVs are effective vehicles for transferring iPSC attributes to adult somatic cells, and hiPSC‐MV‐mediated horizontal transfer of RNAs and proteins to injured tissues may be used for therapeutic tissue repair. In this study, for the first time, we propose a new concept of use of hiPSCs as a source of safe acellular bioactive derivatives for tissue regeneration. Stem Cells   2015;33:2748–2761